2013
DOI: 10.1089/jwh.2013.4394
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Activity and Sedentary Behavior with Biological Markers Among U.S. Pregnant Women

Abstract: Physical activity and sedentary behavior were favorably associated with various biomarkers among pregnant women, suggesting that healthcare providers should encourage pregnant women to participate in safe forms of physical activity behaviors while also reducing their amount of time spent in sedentary behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 36 publications
5
58
1
2
Order By: Relevance
“…Of these, 7 were focused on pregnancy outcomes including gestational weight gain (GWG) and maternal depression [12, 30, 34, 40, 44–46], 5 on metabolic outcomes [10, 36, 44, 47, 49], and 5 on infant outcomes [12, 31, 32, 39, 49]. …”
Section: Resultsmentioning
confidence: 99%
“…Of these, 7 were focused on pregnancy outcomes including gestational weight gain (GWG) and maternal depression [12, 30, 34, 40, 44–46], 5 on metabolic outcomes [10, 36, 44, 47, 49], and 5 on infant outcomes [12, 31, 32, 39, 49]. …”
Section: Resultsmentioning
confidence: 99%
“…A correct bodyweight, regular exercise and a reduction in stressful life events are useful actions in addition to a proper diet including a high intake of fluids, fruits and vegetables, low consumption of salt and protein, and limited carbohydrate . Exercise improves insulin sensitivity, the cornerstone of the association between dyslipidemia and urolithiasis, and is expected to improve Mets components …”
Section: Discussionmentioning
confidence: 99%
“…37 Exercise improves insulin sensitivity, the cornerstone of the association between dyslipidemia and urolithiasis, and is expected to improve Mets components. 38,39 Renal tubular cell injury triggers crystal deposition, and lipid metabolites could be involved in the molecular mechanism of calcium oxalate crystallization in particular. Tsujihata et al showed, in an experimental study, that atorvastatin has an inhibitory effect on renal tubular injury and oxidative stress caused by oxalate crystals, and concluded atorvastatin could help to prevent and treat crystal formation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased physical activity in pregnant women in conjunction with a proper diet was connected with a lower risk of excessive weight gain in pregnancy, cesarean delivery, macrosomia, and neonatal respiratory morbidity [2], had a positive effect on the concentration of cholesterol, C-reactive protein (CRP), and blood pressure [3], and reduced the risk of preeclampsia [4] and gestational diabetes [5]. Regular exercise helped to maintain cardiovascular fitness levels throughout pregnancy, recovery of shape after childbirth [6], and improved sleep quality in pregnant women [7].…”
Section: Introductionmentioning
confidence: 99%